Ventilation of molds for die casting - A. M. Mikhaltsov; A. A. Pivovarchyk (Литьë и металлургия)
This paper describes the factors that affect gas content in castings during pressure molding. The possibility of removing air and gases from the cavity of the mold through the ventilation channels in the process of filling it with liquid metal is considered. It is shown that the previously used assumption about the outflow of gases from the mold as through a hole in a thin wall is not correct. The calculations, taking into account the friction factor in narrow ventilation ducts, showed that the required crosssectional area of the ventilation ducts increases 4–6 times with a depth of 0,12 mm. If the obtained value of the cross-sectional area of the ventilation ducts is not possible to realize, at a given depth, it is proposed to use an accompanying vacuum to solve the problem.